2006
DOI: 10.1109/tap.2005.861560
|View full text |Cite
|
Sign up to set email alerts
|

Analysis and Design of a Cylindrical EBG-Based Directive Antenna

Abstract: Abstract-In this paper, a cylindrical electromagnetic bandgap (CEBG) structure composed of infinite metallic wires is analyzed, designed and used as a model to develop a new reconfigurable directive antenna. This structure is circularly and radially periodic, and it is excited at its center using an omnidirectional source. The analysis is based on calculating the transmission and reflection coefficients of a single cylindrical frequency selective surface (FSS) and then, considering only the fundamental mode in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
74
0
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(75 citation statements)
references
References 15 publications
0
74
0
1
Order By: Relevance
“…Wire에 유기되는 전류를 표현하기 위해 아래와 같은 triangular sub-domain 기저 함수를 이용하였다. 의 공진 특성이 일어날 때, 바깥으로 공급되는 전원이 더 크게 되기 때문이다 [8][10] . …”
Section: 무한 배열 구조를 이용하면 개략적인 전파 특성을 효율unclassified
“…Wire에 유기되는 전류를 표현하기 위해 아래와 같은 triangular sub-domain 기저 함수를 이용하였다. 의 공진 특성이 일어날 때, 바깥으로 공급되는 전원이 더 크게 되기 때문이다 [8][10] . …”
Section: 무한 배열 구조를 이용하면 개략적인 전파 특성을 효율unclassified
“…This coefficient is plotted in Fig. 2 by using the semi-analytical method proposed in [10]. From Fig.…”
Section: Structure With One Layermentioning
confidence: 99%
“…8 and 9, respectively. The coefficient |T 3 | is the response of the structure considering the multiple reflection with the center, whereas the coefficient |t 3 | is the response of the structure if the multiple reflections with the center are not considered [10]. From Figs.…”
Section: Structure With Three Layersmentioning
confidence: 99%
See 1 more Smart Citation
“…Cylindrical Electromagnetic Band Gap (CEBG) structures are radially and circularly periodic, and they present pass-band and stop-band to cylindrical electromagnetic waves [3]. By applying a horn-shaped defect in these structures, it has been shown that a reconfigurable directive pattern can be obtained [4][5][6]. In [4], experimental results for a reconfigurable CEBG-based antenna have been presented, whereas in [5], an analysis of the transmission coefficient of CEBG structures and experimental results for a CEBG directive antenna have been proposed.…”
Section: Introductionmentioning
confidence: 99%